Association Between Liver Fat and Bone Density is Confounded by General and Visceral Adiposity in a Community‐Based Cohort. Issue 3 (2nd February 2021) - Li, Belinda T.; Simon, Tracey G.; Wang, Na; Chung, Raymond T.; Corey, Kathleen E.; Dichtel, Laura E.; Samelson, Elizabeth J.; Kiel, Douglas P.; Long, Michelle T.
Abstract : Objective: Nonalcoholic fatty liver disease (NAFLD) is associated with low bone mineral density (BMD); however, it is not known whether early‐stage NAFLD may be associated with BMD after accounting for BMI or visceral adipose tissue (VAT). Methods: This was a cross‐sectional study of 3, 462 Framingham Heart Study participants who underwent computed tomographic measurement of liver fat, VAT volume, volumetric spine BMD, vertebral cross‐sectional area (CSA), and vertebral compressive strength. This study excluded heavy alcohol consumers. Multivariable linear regression models were used to assess the association between NAFLD and volumetric BMD, CSA, and vertebral compressive strength after accounting for covariates, including BMI or VAT. Results: A total of 2, 253 participants (mean age, 51.2  [SD 10.7] years; 51.1% women) were included. In multivariable‐adjusted models, positive associations between NAFLD and integral BMD, trabecular BMD, and vertebral compressive strength were observed. However, results were attenuated and no longer significant after additionally adjusting for BMI or VAT. NAFLD was observed to be weakly associated with a lower vertebral CSA in adjusted models. Conclusions: In a community‐based cohort, the associations between NAFLD and BMD and vertebral strength were confounded by BMI and VAT. However, NAFLD was associated with a reduced vertebral CSA in adjusted models.